Characterisation of subpopulations of myeloid cells in infantile haemangioma. Issue 7 (1st April 2015) - Tan, Elysia M S; Chudakova, Daria A; Davis, Paul F; Brasch, Helen D; Itinteang, Tinte; Tan, Swee T
Abstract : Aims: Cells expressing markers of mast cells, macrophages and dendritic cells have previously been demonstrated within the interstitium of infantile haemangioma (IH). This study characterised these myeloid cellular subpopulations within IH. Methods: Immunohistochemical staining was performed on proliferating and involuted IHs for the expression of Nanog, tryptase, CD163, DC-SIGN and CD45. The presence of mRNA corresponding to Nanog, tryptase α/β-1, tryptase β-2, CD163 and DC-SIGN was confirmed by NanoString and RT-PCR in snap-frozen IH tissues. Results: Immunohistochemical staining showed expression of Nanog by interstitial phenotypical mast cells within proliferating IH, which were separate from the interstitial M2-polarised macrophages that also expressed DC-SIGN, a dendritic cell marker. These two myeloid cellular subpopulations in IH did not express the pan-haematopoietic marker, CD45. Conclusions: There are two interstitial subpopulations of myeloid cells within IH: phenotypical mast cells which also express Nanog, indicating a primitive phenotype; and M2-polarised macrophages which also express DC-SIGN.